Reducing diabetes burnout syndrome using self-instructional training - Nuari, Nian Afrian; Rahman, Handono Fatkhur; Wahid, Abdul Hamid (International Journal of Public Health Science (IJPHS), 2023)
Patients with type 2 diabetes mellitus (T2DM) experienced diabetes burnout, which influences the patient’s daily living. Some treatments had been introduced to reduce this burnout, but self-instructional training method remained unknown for its effectiveness. This study was aimed to analyse the influence of self-instructional training toward diabetes burnout syndrome. This research was a quasy-experimental study involving patients with diabetes mellitus type 2. About 72 respondents were chosen using purposive sampling. This study divided the respondents into control and treatment groups. The treatment group gained self-instructional training in 4 meetings. Data was obtained from pre-test and post-test using diabetes burnout scale questionnaire and analysed with Paired T-test and Independent T-test. Study results showed that the treatment group had a significant decrease in diabetes burnout (severe to low level) (p=0.000). Diabetes burnout score among treatment group was lower compared to the control group (24.69±4.73; 19.19±4.24). In the control group, there was no significant statistical reduction about diabetes burnout (p=0.110). Besides, this study presented the difference diabetes burnout syndrome between treatment and control group (p=0.000; p<0.05). This study showed self-instructional training could minimize the occurrence of diabetes burnout syndrome among T2DM patients. This method has been proven to influence patient’s behaviour positively.